2018
DOI: 10.1371/journal.pone.0195320
|View full text |Cite
|
Sign up to set email alerts
|

Early-life conditions and health at older ages: The mediating role of educational attainment, family and employment trajectories

Abstract: ObjectivesWe examine to what extent the effect of early-life conditions (health and socioeconomic status) on health in later life is mediated by educational attainment and life-course trajectories (fertility, partnership, employment).MethodsUsing data from the Survey of Health, Ageing and Retirement in Europe (N = 12,034), we apply, separately by gender, multichannel sequence analysis and cluster analysis to obtain groups of similar family and employment histories. The KHB method is used to disentangle direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 45 publications
9
59
1
8
Order By: Relevance
“…At the same time, our study observed that the population with college degrees or higher had lower CVD morbidity (data not shown), which is consistent with previous studies that have reported that lower education levels may contribute to CVD risk factors 39 . It is possible that more educated subjects may benefit from the increased health knowledge and a healthier life style 40,41 . Regarding hypertension, we found an inverse association between LTL and CVD risk in people without hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, our study observed that the population with college degrees or higher had lower CVD morbidity (data not shown), which is consistent with previous studies that have reported that lower education levels may contribute to CVD risk factors 39 . It is possible that more educated subjects may benefit from the increased health knowledge and a healthier life style 40,41 . Regarding hypertension, we found an inverse association between LTL and CVD risk in people without hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals' socioeconomic status is one of the most important background determinants of fertility and as such can be considered as a distal determinant also for the demography of grandparenthood. In a recent study, Arpino, Gumà, and Julià (2018) found that early-life (e.g., parental socioeconomic background) and childhood conditions (e.g., health) influence fertility and partnership histories through their influence on educational attainment. Therefore, early-life conditions and education may be thought as distal determinants of grandparenthood outcomes because of their indirect effect operating through their influence on family histories.…”
Section: Mechanisms Influencing the Demography Of Grandparenthoodmentioning
confidence: 99%
“…Children's happiness and health are known to be important societal values [1,2]. It is generally considered that lifetime health outcomes and socioeconomic status are largely determined by an appropriate and stable environment at the start of life [3].…”
Section: Introductionmentioning
confidence: 99%